The Association of Cardiovascular Risk Factors and Depression of an adult Austrian Population. (2nd July 2022) - Hinterbuchner, K; Haudum, C W; Hutz, B; Kolesnik, E; Schmidt, A; Zirlik, A; Pieber, T R; Verheyen, N; Obermayer-Pietsch, B; Lohrmann, C; Grossschaedl, F; Colantonio, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): "Austrian Research Fund (COMET K-project No. 825329)" Introduction: Depression has been recognized as a cardiovascular (CVD) risk factor. However, depression is often under-recognized and larger attention should be given to this frequent problem, also in relation to CVD sequelae. There are differences in prevalence of CVD risk factors and CVD care and prevention in Europe. Therefore, it is vital to identify the focus of CVD prevention to implement specific and country-based programs to reduce CVD burden, especially for people with depression. Purpose: The aim of this study is to investigate the association between common CVD risk factors hypertension, body mass index (BMI), and smoking with the severity of depression in an adult Austrian population and to characterize sex-related differences. Method: This current thesis is a cross-sectional study examining the baseline data of the population from the BioPersMed (Biomarkers of Personalized Medicine) cohort at our Medical University. The initial non-probability recruitment started between 2011 and 2015, resulting in a study population of 1, 022 adult men and women who live in the greater Graz area. Three CVD risk factors were examined for this paper and assessed by trained doctors and nurses at baseline: self-reported diagnosis of hypertension, self-reported smoking status, and BMI (kg/m 2 ) by measuring the height and weight of each participant. The PHQ-9 (Patient Health Questionnaire) was analyzed by recording the total score value in three groups. Descriptive statistics, statistical correlation analysis, and an ordinal regression analysis was performed. Results: 977 participants were included in the data analysis, with a mean age of 57.3 years. More than half of the participants (56%) were female. Results show a significant association between hypertension and the severity of depression (p<0.01) and between males and all three CVD risk factors, and between females and overweight. People with hypertension and elevated BMI, adjusted for age, sex, diagnosis of depression, and smoking were more likely to fall into a higher level of depression (BMI: increase of 0.033 in the log odds, p<0.5; hypertension: increase of 0.339 in the log odds, p<0.01). Moreover, men were more likely to show a lower level of depression than women (decrease of 0.435 in the log odds, p<0.5). Conclusion: This is the first cross-sectional study to examine the association between CVD risk factors and the severity of depression in an adult Austrian population. Further research for causality and longitudinal analyses in a larger sample size are recommended to thoroughly examine and confirm these findings. The results are an important indication for CVD prevention programs in Austria to incorporate specific screening (CVD and Depression) and management of cardiovascular risk factors in their protocols and readapt them according to depression severity.